Management Intensity and Transportation Development - Farmer, Richard N. (Academy of Management Journal, 1965)
The article addresses the importance of effective management of modes of transportation and infrastructure in developing nations. The article focuses on managerial intensity in both industrial transportation management as well as government management of transportation, including the design and construction of infrastructure and the regulation of the transportation industry. Additionally, the article addresses the social goals which invariably are tied to government management of transportation. The author develops several hypotheses and conclusions, advocating simple, less intensive management of transportation systems that foster entrepreneurial education and minimize costs.